Penguatan Hukum Hak Cipta Atas Karya Seni Buatan AI di Indonesia dalam Rangka Penguatan Sektor Industri Kreatif 5.0 - Putri, Rizqya Nafila; Nursalamah , Prameswari Aura; Monica , Annisa; Putri , Delasari Krida (Wacana Hukum, 2024)
AI made human work easier in creating many things, like works of art. However, this is worrying for creators or owners. They are concerned about fulfilling exclusive rights to works of art. AI is part of technological developments that should be used as a tool for creators to create works of art. Therefore, clear boundaries are needed regarding how much AI can be used by creators as a tool in creating works of art so there is no reduction in the value of the creator's own efforts and creativity. The type of research that the author uses is applied descriptive with a qualitative nature. The inductive method is applied to analyze and process data which is linked to existing theories and laws and regulations. The author analyzes the comparison of copyright law protection in Indonesia and in the United States regarding works of art created by AI.